Study the effect of injection pressure of a mixture of diesel fuel and vegetable oil on exhaust emissions of diesel engines by simulation - Trung Pham Dinh; Nghia Mai Duc; Tuan Ho Duc (E3S Web of Conferences, 2024)
Biofuels are interested in using alternative fuel in diesel engines because those are friendly to the environment and can be recycled. However, characteristics of chemical and physical differences compared to diesel fuel. While using the fuel injection system of an engine must be adjusted. Computational Fluid Dynamics KIVA-3V software allows simulation of the working cycle of the engine with injection pressure effect. This paper presents the results of a simulation study of B15 biofuel used on the 4CHE Yanmar diesel engine, and the fuel injection pressure was adjusted at 210, 220, 230, and 240 bar within the limits of high-pressure pump adjustment. The results showed that the soot emissions of the engine were lowest at 230 bars.